2019
DOI: 10.3389/fphar.2018.01494
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathologic and Prognostic Significance of Programmed Cell Death Ligand 1 (PD-L1) Expression in Patients With Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Programmed cell death ligand 1 (PD-L1) expression has been shown to correlate with poor prognosis in diverse human cancers. However, limited data exist on the prognostic and clinicopathologic significance of PD-L1 expression in prostate cancers (PCa), and the curative effect of anti-PD-1/PD-L1 therapy remains controversial. In this systematic review and meta-analysis, we aimed to evaluate the prognostic and clinicopathologic value of PD-L1 in PCa.Methods: We performed a systematic literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 50 publications
(79 reference statements)
1
27
0
1
Order By: Relevance
“…A meta-analysis involving 13 studies showed that a high PD-L1 expression could predict a shorter OS (HR = 1.57, 95% CI = 1.09–2.27, P < 0.00001) and poorer DFS (HR = 2.07, 95% CI = 1.20–3.58, P = 0.009) in hepatocellular carcinoma (15). Another study also demonstrated a significant association of PD-L1 expression with a poor biochemical recurrence-free survival (BCR-FS) (HR = 1.78; 95% CI = 1.39 to 2.27; p < 0.00001) in prostate cancer (46). Wang et al showed an association of PD-L1 expression with a poor OS in RCC (47).…”
Section: Discussionmentioning
confidence: 92%
“…A meta-analysis involving 13 studies showed that a high PD-L1 expression could predict a shorter OS (HR = 1.57, 95% CI = 1.09–2.27, P < 0.00001) and poorer DFS (HR = 2.07, 95% CI = 1.20–3.58, P = 0.009) in hepatocellular carcinoma (15). Another study also demonstrated a significant association of PD-L1 expression with a poor biochemical recurrence-free survival (BCR-FS) (HR = 1.78; 95% CI = 1.39 to 2.27; p < 0.00001) in prostate cancer (46). Wang et al showed an association of PD-L1 expression with a poor OS in RCC (47).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, Ni’s study also reported the expression of PD-L1 was positively correlated with the lymph node metastasis in colorectal cancer [29]. The prognostic value was also presented in other solid malignancies including prostate cancer [30], esophageal squamous cell carcinoma [31], glioma [32], Osteosarcoma [33], and non-small cell lung cancer [34]. The results of the present meta-analysis were in line with the results of other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SPOP mutation compromises of ubiquitin-mediated PD-L1 degradation leading to increased PD-L1 levels and reduced numbers of infiltrating lymphocytes in prostate cancers [125]. Another recent study showed that phosphorylated RB inhibits NF-kB activation and PD-L1 expression: in patients samples phosphorylated RB inversely correlates with PD-L1 levels [397]. Interestingly, the expression of a phosphorylation-mimetic peptide in prostate cancer cells suppresses radiotherapy-induced upregulation of PD-L1 and augments the therapeutic efficacy of radiation in vivo [397].…”
Section: Sensitivity Of Prostate Cancer To Immunotherapymentioning
confidence: 99%